(untitled) (University Arena, 2025)
Background. Psychomotricity, being a part of applied psychology, studies motor functions, integrated and coordinated by the psychic functions. Psychomotricity manifests itself as an ability as well as a complex process, which regulates individual behaviour. We can also define it as the art of controlling one’s behaviour. The present paper deals with improving elementary motric behaviour: achieving general movement control using sports dance. Objectives. This paper deals with the way in which applied programs made beneficiaries more aware of their bodies, also improving their cognitive function. The purpose of this paper is also represented by the assessing, using psychomotricity, of the coordination component and changes which appeared after applying the two programs and also by the assessing of the comparative study of these changes. Methods. To draw up this paper, I have used the following methods: the bibliographical research method, the assessing and data testing one, mathematical statistics methods and also the graphic one. Results. Both groups improve their initial parameters as a result of the training and learning process. However, the group which has done the exercises improved more than the group which simply watched. This observation leads us to the same conclusion: individualized preparation is superior compared to the face-to-face traditional one. Conclusion. We can also explain why the results achieved by the experimental group are superior on account of the methodology used for implementing training strategies. During the psychomotor training process, the exercises focused on acquiring certain types of behaviour, allowing students to slowly apprehend the basic moves. This, in turn, led to a more accurate representation concerning the human body moves and its segments.